2022
DOI: 10.1167/tvst.11.9.28
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Optical Coherence Tomography of Peripapillary Retinal Nerve Fiber Layer Reflectivity in Glaucoma

Abstract: Purpose To evaluate the clinical utility of visible light optical coherence tomography (VIS-OCT) and to test whether VIS-OCT reflectivity and spectroscopy of peripapillary retinal nerve fiber layer (pRNFL) are correlated with severity of glaucoma, compared with standard-of-care OCT thickness measurements. Methods In total 54 eyes (20 normal, 17 suspect/preperimetric glaucoma [GS/PPG], 17 perimetric glaucoma [PG]) were successfully imaged with complete datasets. All the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The illumination power on pupil was less than <0.25 mW (VIS) and 0.9 mW (NIR), respectively, meeting the safety standards of the ANSI for ophthalmic instrument. Details of the calculation can be seen in the supplementals of our previous publication 30 . We used a tunable lens to correct the spherical refractive error.…”
Section: Methodsmentioning
confidence: 99%
“…The illumination power on pupil was less than <0.25 mW (VIS) and 0.9 mW (NIR), respectively, meeting the safety standards of the ANSI for ophthalmic instrument. Details of the calculation can be seen in the supplementals of our previous publication 30 . We used a tunable lens to correct the spherical refractive error.…”
Section: Methodsmentioning
confidence: 99%
“…Since its conception in the 1990s, optical coherence tomography (OCT) has been one of the most influential imaging methods in biophotonics and has revolutionized clinical practice in ophthalmology 1 . Visible light optical coherence tomography (VIS-OCT) is a burgeoning modification of OCT that uses visible instead of near-infrared (NIR) illumination and has been demonstrated for preclinical and clinical ophthalmic imaging 2 4 . One advantage of VIS-OCT is that visible wavelengths demonstrate higher levels of backscattering from biological tissues than longer near-infrared wavelengths 5 and reveal distinct spectral contrast in imaging pigmentation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Pi et al measured, quantitatively, retinal blood oxygen saturation in vitro and in rats [26]. Recently, Song et al have shown that the reflectance signal from VIS-OCT could better distinguish glaucoma subjects from normal eyes than thickness measurements from OCT [27]. However, the acquisition time was 2.6 sec at 50 kHz A-line speed and the laser power at the pupil was 0.25 mW for a wavelength range of 545 to 580 nm.…”
Section: Introductionmentioning
confidence: 99%